Association of rare variation in the glutamate receptor gene SLC1A2 with susceptibility to bipolar disorder and schizophrenia - Fiorentino, Alessia (Eur J Hum Genet, 2015)
The SLC1A2 gene encodes the excitatory amino acid transporter 2 (EAAT2). Glutamate is the major mediator of excitatory neurotransmission and EAAT2 is responsible for clearing the neurotransmitter from the synaptic cleft. Genetic variation in SLC1A2 has been implicated in a range of neurological and neuropsychiatric conditions including schizophrenia (SZ), autism and in core phenotypes of bipolar disorder (BD). The coding and putative regulatory regions of SLC1A2 gene were screened for variants using high resolution melting or sequenced in 1099 or in 32 BD subjects. Thirty-two variants were detected in the SLC1A2 gene. Fifteen potentially etiological variants were selected for genotyping in 1099 BD and 1095 control samples. Five amino acid changing variants were also genotyped in 630 participants suffering from SZ. None of the variants were found to be associated with BD or SZ or with the two diseases combined. However, two recurrent missense variants (rs145827578:G>A, p.(G6S); rs199599866:G>A, p.(R31Q)) and one recurrent 5′-untranslated region (UTR) variant (ss825678885:G>T) were detected in cases only. Combined analysis of the recurrent-case-only missense variants and of the case-only missense and 5′-UTR variants showed nominal evidence for association with the combined diseases (Fisher's P=0.019 and 0.0076). These findings are exploratory in nature and await replication in larger cohorts, however, they provide intriguing evidence that potentially functional rare variants in the SLC1A2 gene may confer susceptibility to psychotic disorders.